Fabricating 3D Metastructures by Simultaneous Modulation of Flexible Resist Stencils and Basal Molds - Cai, Hongbing (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.